Turkish Adaptation of the Social Media Disorder Scale in Adolescents - Savci, Mustafa; Ercengiz, Mustafa; Aysan, Ferda (Turkish Neuropsychiatry Assoc-Turk Noropsikiyatri Dernegi, 2018)
Introduction: The aim of this study is to determine the reliability and validity of the Turkish form of Social Media Disorder Scale (SMDS) in adolescents which is developed using the diagnostic criteria of DSM-V Internet Gaming Disorder. Methods: Validity and reliability analysis of SMDS was conducted through four different sample of 553 adolescents who use social media every day for the past 1 year, and have at least one social media account. Results: The construct validity of SMDS was examined with Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). After EFA, it was seen that the items of SMDS grouped under 1 factor which eigenvalue is above 1. This one factored structure explains about half of the total variance. One factored structure obtained from EFA was tested with CFA in two different samples. After CFA, it was shown that one factored SMDS model has good cohesion values in each two samples. Concurrent validity of the SMDS have been examined period of the use of social media, social media account number, self-discipline, impulsivity, positive affect, negative affect and social connectedness. At the result of the analysis, it was found that SMDS is positive correlated with duration of the use of social media, social media account number, negative emotions and impulsivity; negative correlated with self-discipline, social connectedness. and positive emotions. The reliability of SMDS was examined with test-retest method and Cronbach's a internal consistency reliability coefficient in three different samples. Analysis showed that Cronbach's a internal consistency reliability coefficients and test-retest reliability coefficient were found to be adequate. SMDS item analysis was carried out in three different samples. It was found that corrected item-total correlation coefficients of the SMDS items are in the range of accepted values in the literature t-test results for 27% sub-super group item comparisons are significant for all items in each three samples. Conclusion: According to the results of EFA, CFA, criterion-related validity, reliability analysis, and item analysis of SMDS, the Turkish form of SMDS is a valid and reliable instrument.
Keywords: Sosyal media disorder; social media addiction; adolescent; exploratory factor analysis; confirmatory factor analysis